Pengaruh Motivasi Kerja Dan Disiplin Kerja Terhadap Kinerja Karyawan : Studi pada salah satu perusahaan BUMN di Jawa Barat - Chrisvan Caissar; Aan Hardiyana; Adhie Fasha Nurhadian; Kadir Kadir (Acman: Accounting and Management Journal, 2022)
This study aims to determine the effect of work motivation and work discipline on employee performance. The object of research is one of the state-owned companies in West Java. The number of respondents in this study was 50 employees. The author uses path analysis techniques to analyze the effect of work motivation and work discipline on employee performance. The study results proved that there was a significant influence of work motivation and work discipline on employee performance. Therefore, to improve employee performance, companies should need to provide motivation to their employees and monitor the performance improvement of each employee so that if employee motivation and discipline are good, good performance will also create. For example, the company provides bonuses/incentives to employees who have worked well following company regulations. So that employees are motivated and disciplined, thus employees will continue to improve their performance.